2009
DOI: 10.1007/s00284-009-9535-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Y-Family DNA Polymerases YqjH and YqjW in Protecting Sporulating Bacillus subtilis Cells from DNA Damage

Abstract: The role played by the Y-family DNA polymerases YqjH and YqjW in protecting sporulating cells of Bacillus subtilis from DNA damage was determined. The absence of either yqjH and/or yqjW not only reduced sporulation efficiency but also sensitized the sporulating cells to hydrogen peroxide, tert-butylhydroperoxide (t-BHP), mitomycin-C (M-C), and UV-C radiation. Moreover, these DNA-damaging agents increased the mutation frequency of wild-type sporulating cells to 4-azaleucine, but the production of mutants was Yq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Therefore, we tested the idea that the mutagenesis observed in the ⌬recD2 strain is caused by increased usage of lesion bypass DNA polymerases in the absence of RecD2. In B. subtilis, polymerases PolY1 (YqjH) and PolY2 (YqjW) and essential replicative polymerase DnaE have been shown to be involved in lesion bypass in vitro or in vivo (46)(47)(48)(49)(50) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tested the idea that the mutagenesis observed in the ⌬recD2 strain is caused by increased usage of lesion bypass DNA polymerases in the absence of RecD2. In B. subtilis, polymerases PolY1 (YqjH) and PolY2 (YqjW) and essential replicative polymerase DnaE have been shown to be involved in lesion bypass in vitro or in vivo (46)(47)(48)(49)(50) …”
Section: Resultsmentioning
confidence: 99%
“…The data shown here are also presented in more detail in Table S2 in the supplemental material. 50 defined minimal medium to an OD 600 of 0.4 to 0.6 with 1% arabinose and 0.125% xylose prior to treatment. Cultures were left untreated prior to imaging.…”
Section: Fig 2 Deletion Of Recd2 Increases Spontaneous Mutagenesis Inmentioning
confidence: 99%
“…This endospore can remain dormant for long periods of time, until it encounters the appropriate conditions to germinate and resume growth (42). It has been proposed that the formation of the spore may potentially be compromised by damaging the chromosomes of either cell compartment and that the sporulating cell presumably relies on mechanisms to sense, repair, or even tolerate DNA damage in order to generate the two cell types (31). In support of these notions, results have revealed that defects in chromosome partitioning or DNA damage can delay sporulation at the level of Spo0A activation (4,18) and that DisA, a scanning checkpoint protein, temporarily blocks the initiation of sporulation when DNA damage is encountered (2).…”
mentioning
confidence: 99%
“…B. subtilis possesses an arsenal of preventive and repair mechanisms to counteract the mutagenic and deleterious effects of these insults (5,10,28,29,30,31,33,38,53,55). The expression of genes that prevent and repair genetic insults in this bacterium is regulated in time and space by gene circuitries that respond to developmental and environmental conditions during growth and cell differentiation (6,23,24,28,34,38,49,54,55).…”
mentioning
confidence: 99%
“…subtilis relies on several repair mechanisms to counteract the adverse effects of intra-and extracellular factors that generate a myriad of insults to DNA (3,7,11,24,49,64). DNA repair genes are differentially expressed during growth and/or sporulation, and the physiological roles played by their encoded products have been demonstrated in several cases (45,47,50,62). Analysis of the genome of B. subtilis reveals the presence of a uracil-DNAglycosylase-encoding gene (ung) that can be classified into family 1 of the UDGs.…”
mentioning
confidence: 99%